VULNERABILITY OF VICTIMS OF SEXUAL VIOLENCE FROM THE PERSPECTIVE OF NATIONAL LAW AND CUSTOMARY LAW IN PAPUA - Erllyn Vilenchia Rumfeka; Rahmat Syahril Ulath (Papua Law Review, 2026)
Sexual violence remains a serious concern in Indonesia, particularly in Indigenous communities where victims often encounter legal, cultural, and social barriers to accessing justice. In Papua, customary values and community-based dispute resolution mechanisms continue to play an important role in responding to criminal acts, including sexual violence. This study examines the vulnerability of victims from a victimological perspective by exploring the interaction between state law and customary law in fulfilling victims' rights. Employing a normative legal research method, the study analyzes the implementation of Law Number 12 of 2022 on the Crime of Sexual Violence (TPKS Law) in relation to the realities of customary communities in Papua. The findings indicate that although the TPKS Law provides a comprehensive legal framework for victim protection, its implementation remains limited at the local level. Victims continue to experience difficulties in obtaining restitution, access to safe shelters, and long-term psychological recovery due to bureaucratic obstacles, limited institutional capacity, and inadequate coordination between formal legal institutions and customary authorities. In several Indigenous communities, customary dispute resolution may prioritize social harmony and communal reconciliation over victims' rights, potentially limiting access to comprehensive legal protection. This study emphasizes the importance of strengthening collaboration between state institutions and customary leaders to ensure that victim-centered justice is achieved while respecting the cultural values and legal traditions of Indigenous Papuan communities